The use of mobile information and communication technologies in the process of teaching higher mathematics - Лінник, О. П.; Рашевська, Н. В. (Pedagogy of Higher and Secondary Education, 2021)
In the article the model of blended learning higher mathematics in universities and technical possibilities of building this model by means of mobile information and communication technologies. An example of a mobile system to support learning and mobile system computer mathematics.